Síntese de 1,2,3-triazóis-1,4-dissubstituídos contendo organocalcogênios derivados de 4-(azidometil)-2-fenil-1,3-calcogenazóis via reação de cicloadição 1,3-dipolar - Bernardy, Silvia (2020)
In this present work, an unprecedented series of 4-((4-((arylchalcogen)methyl)-1H-1,2,3-triazol-1-yl) methyl)-2-phenylchalcogenazole 20 and 21 was synthesized with interest in the potential biological, because to the presence of different heterocyclic nucleus. The 4-(chloromethyl)-2-phenylchalcogenazoles 6 and 7 were obtained through a cyclization reaction of benzochalcogenoamides 3 and 4 with 1,3- dichloroacetone 5, with yields of 55% and 80%. For the synthesis reaction of 4-(azidomethyl)-2-phenyl- 1,3-chalcogenazoles 10 and 11, were used 4-(chloromethyl)-2-phenylchalcogenazoles 6 and 7, potassium iodide and sodium azide 9, of the yields were 55% and 60%. Through the Click reaction type, catalyzed by copper iodide, between 4-(azidomethyl)-2-phenyl-1,3-chalcogenazoles (10; 11) and propargyl alcohol 12, the formation of (1-((2-phenylchalcogenazo-4-yl)methyl)-1H-1,2,3-triazo-4-yl)methanol 13 and 14, with yields of 88% and 76%, respectively. Subsequently, the protection of the alcohol function of (1-((2- phenylchalcogenazol-4-yl)methyl)-1H-1,2,3-triazo-4-yl)methanol 13 and 14 was performed with mesyl chloride 15, where yields varied from 67% to 60% in obtaining (1-(((2-phenylchalcogenazol-4-yl)methyl)- 1H-1,2,3-triazol-4-yl) methanesulfonate 16 and 17, respectively. From the nucleophilic substitution reaction, optimized, between (1-(((2-phenylchalcogenazol-4-yl)methyl)-1H-1,2,3-triazol-4- yl)methanesulfonates (16, 17) and diphenyl dichalcogenides 18 and 19 take to the formation of the products desired, the 4-((4-((arylchalcogen)methyl)-1H-1,2,3-triazol-1-yl) methyl)-2-phenylchalcogenazole 20 and 21, with yields of 47% to 94%.